ESTIMATION OF SOME IMPORTANT ESSINTIAL ELEMENTS LEVELS Se, Zn AND Fe IN THE SICKLE CELL ANEMIA PATIANTS SERUM IN BASRAH. - Awad, Nadhum A. (University of Thi-Qar Journal of Science, 2013)
This study was performed to determine some essential elements such as selenium, zinc, and Iron in the serum of the sickle cell anemia patients and the results were compared with that of a control healthy group.The obtained results showed clear deficiency in selenium levels in patients serum (60-85) ng/ml compared with healthy control (95 – 130) ng/ml.The result show a high deficiency in zinc level of sickle cell serum (0.70 –1.25) g/ml as compared with health control (0.9 – 1.25) g/ml.On the other hand Iron shows a high level in patient serum (10 – 19) g/ml as compared with healthy control (9.0 – 13) g/ml.